Statistical learning and language acquisition - Williams, John N. (Studies in second and foreign language education, 2012)
This volume brings together contributors from cognitive psychology, theoretical and applied linguistics, as well as computer science, in order to assess the progress and future directions of statistical learning research. The textcritically examines the role of statistical learning in language acquisition. Contributors agree that statistical learning plays a central role in language acquisition, but each offerdiffering perspectives. The book promotes the development of the field by fostering discussion and collaborations across disciplinary boundaries.